Nursing report of a patient with dermal toxic reaction caused by antitumor drugs (1例抗肿瘤药物引起皮肤毒性反应患者的护理体会) - GONG Yonghong (龚永红); HU Wei (胡薇); GUI Meifen (桂梅芬); HAO li (郝丽) (中西医结合护理)
This paper summarized the skin care process of a patient with sigmoid colon malignant tumor after two courses of chemotherapy and targeted therapy with Capecitabine and Cetuximab injection. The application of licorice oil, a traditional Chinese Medicine, instead of normal saline for debridement can promote the softening of scab and relieve the pain of debridement. During the treatment, comprehensive nursing interventions on mental health, dietary and home-based education were carried out to reduce the risk of recurrence. (本文总结1例抗肿瘤药物引起皮肤毒性反应患者的护理经验。应用中药制剂甘草油替代生理盐水进行清创, 促进痂皮软化, 减轻患者清创疼痛; 同时给予患者心理、饮食、居家护理指导, 避免复发。)